Lean Management and Lean Leadership in Health - Gülcan Şantaş (Association of Nurse Managers, 2020)
The lean management approach enables to create a culture in health institutions where continuous improvements occur in order to increase the satisfaction of patients and other stakeholders. There is a need for the presence, and pioneering of a leader in the implementation of the lean management approach, and in spreading this approach within the organization which has become increasingly important in health institutions in recent years. In the future, it has been thought that the lean management practices and the initiatives to avoid extravagancy in health institutions will be more frequently discussed in Turkey. Within this context this study focuses on the conceptual framework of lean management and lean leadership in health institutions.